Rhino ranch : a novel - McMurtry, Larry (Simon & Schuster, 2009)
Returning home to recover from a near-fatal heart attack, Duane discovers that he has a new neighbor: the statuesque K. K. Slater, a quirky billionairess who's come to Thalia to open the Rhino Ranch, dedicated to the preservation of the endangered black rhinoceros. Despite their obvious differences, Duane can't help but find himself charmed by K.K.'s stubborn toughness and lively spirit, and the two embark on a flirtation that rapidly veers toward the sexual -- but the return of Honor Carmichael complicates Duane's romantic intentions considerably.